Pain and factors that affect its definition as defined by preschool age children: a qualitative study - Inal, Sevil (2018)
The aim of this study was to determine the definitions of pain by pre-school age children and factors that affect these definitions. The study was conducted on children aged between four and six years (N=146) in the city of Karaman in Turkey. Qualitative and quantitative research design were used together in this study. This study’s qualitative tradition method was phenomenologic research.The data were assessed using descriptive statistics and thematic analysis. The children’s definitions of pain were found to be affected by their hospital and daily life experiences. The preschool age children generally defined pain in similar ways, and everything that made children feel pain made them think about it. Sometimes their family members, hospital equipment, and health staff lead them to think about pain.